Beispiel Nr: 11
$ \text{Gegeben:}\\\text{Breite} \qquad b \qquad [m] \\ \text{Länge} \qquad a \qquad [m] \\ \\ \text{Gesucht:} \\\text{Umfang} \qquad U \qquad [m] \\ \\ U = 2\cdot a + 2\cdot b\\ \textbf{Gegeben:} \\ b=\frac{15}{17}m \qquad a=0m \qquad \\ \\ \textbf{Rechnung:} \\ U = 2\cdot a + 2\cdot b \\ b=\frac{15}{17}m\\ a=0m\\ U = 2\cdot 0m + 2\cdot \frac{15}{17}m\\\\U=1\frac{13}{17}m \\ \small \begin{array}{|l|} \hline b=\\ \hline 0,882 m \\ \hline 8,82 dm \\ \hline 88,2 cm \\ \hline 882 mm \\ \hline 8,82\cdot 10^{5} \mu m \\ \hline 0,000882 km \\ \hline \end{array}\\ \small \begin{array}{|l|} \hline a=\\ \hline 0 m \\ \hline 0 dm \\ \hline 0 cm \\ \hline 0 mm \\ \hline 0 \mu m \\ \hline 0 km \\ \hline \end{array}\\ \small \begin{array}{|l|} \hline U=\\ \hline 1,76 m \\ \hline 17,6 dm \\ \hline 176 cm \\ \hline 1,76\cdot 10^{3} mm \\ \hline 1,76\cdot 10^{6} \mu m \\ \hline 0,00176 km \\ \hline \end{array}\\$